Early childhood stunting and later life outcomes: a longitudinal analysis - Deshpande, Ashwini; Ramachandran, Rajesh (Economics and human biology, 2022)
Using longitudinal data from four countries-Ethiopia, India, Peru and Vietnam- we show that early childhood stunting is highly persistent as measured by the association between stunting status in early childhood and stunting status at age 15. Stunting in early childhood is associated with lower grade completion by age 22 and has a negative relationship with cognition as measured by math, language and reading scores at ages 8, 12 and 15. Stunting in early childhood is also associated with poorer subjective assessment of a child’s health at age 15. Analyzing determinants, we show that lack of preventive care and economic shocks are associated with an increase in the probability of stunting in early childhood.